Detection of Exosomal PD-L1 RNA in Saliva of Patients With Periodontitis - Yu, Jialiang; Lin, Yusheng; Xiong, Xiao; Li, Kai; Yao, Zhimeng; Dong, Hongmei; Jiang, Zuojie; Yu, Dan; Yeung, Sai-Ching Jim; Zhang, Hao (Frontiers in Genetics, 2019)
Periodontitis is the most prevalent inflammatory disease of the periodontium, and is related to oral and systemic health. Exosomes are emerging as non-invasive biomarker for liquid biopsy. We here evaluated the levels of programmed death-ligand 1 (PD-L1) mRNA in salivary exosomes from patients with periodontitis and non-periodontitis controls. The purposes of this study were to establish a procedure for isolation and detection of mRNA in exosomes from saliva of periodontitis patients, to characterize the level of salivary exosomal PD-L1, and to illustrate its clinical relevance. Bioinformatics analysis suggested that periodontitis was associated with an inflammation gene expression signature, that PD-L1 expression positively correlated with inflammation in periodontitis based on gene set enrichment analysis (GSEA) and that PD-L1 expression was remarkably elevated in periodontitis patients versus control subjects. Exosomal RNAs were successfully isolated from saliva of 61 patients and 30 controls and were subjected to qRT-PCR. Levels of PD-L1 mRNA in salivary exosomes were higher in periodontitis patients than controls (p<0.01). Salivary exosomal PD-L1 mRNA showed significant difference between the stages of periodontitis. In summary, the protocols for isolating and detecting exosomal RNA from saliva of periodontitis patients were, for the first time, characterized. The current study suggests that assay of exosomes-based PD-L1 mRNA in saliva has potential to distinguish periodontitis from the healthy, and the levels correlate with the severity/stage of periodontitis.